Characteristics of Endometrial Cells and the Factors that Influence the Implantation Process - Larasati, Manggiasih Dwiayu; ita, ita (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
Infertility is a global health problem faced by 8 - 10% of couples in the world. It means 50 - 80 million couples have infertility problem. Knowledge about comprehensive and profound reproductive system is main asset for managing infertility. When look at various factors those contribute to women infertility, so the role of endometrium is very important. The optimal endometrial environment for receiving blastocyst is a major factor in the process of implantation and pregnancy. This study attempts to review and compare sources from research article, case report, and reviews from reputable international journals. Research by Germeyer et all (2010) shows that optimal growth and development of endometrium are factors those greatly contributes for successful implantation which is continued to pregnancy. The same thing is revealed by Neykova review (2020) which states the success implantation process is determined by the quality of the embryo, the readiness of the endometrium to accept the result of conception and interaction, and communication of molecular cells. Currently, various studies are being developed for evaluating endometrium condition through genetic improvement, the use of new biomarkers, non-invasive method even sophisticated method such as proteomic technique Endometrial Receptivity Assay (ERA) in order to solve women infertility problem.